Investigation on repair of tension cracks in reinforced concrete panels. (15th October 2021) - Ahmadi, Alireza; Kianoush, M. Reza; Moslemi, Mehdi; Lachemi, Mohamed; Siad, Hocine; Booya, Emad
Highlights: GFRP was found quite effective in waterproofing damaged normal concrete members. Sudden growth in crack width and leakage rate observed in epoxy repaired specimens. ECC proved to be a proper choice for repairing liquid containing concrete structures. Use of fly ash resulted in a superior cracking and leakage behavior of ECC. Slag resulted in a higher tensile capacity but a more brittle behavior than fly ash. Abstract: This research concentrates on repair of tension cracks in RC panels subjected to direct tensile loading and hydrostatic water pressure by incorporating high-performance materials including High-strength epoxy, Glass Fiber Reinforced Polymer (GFRP) laminate, Engineered Cementitious Composite (ECC) slag, and ECC fly ash. The findings are directly applicable to construction and repair of structures in which crack control and liquid tightness are critical such as liquid containing structures. The test setup simulates repairing internal surface of a cracked wall segment of a containment exposed to internal hydrostatic pressure. The study showed the applicability of ECC fly ash in repairing RC specimens with the ability to restore the structural strength along with improving the cracking and leakage behavior. GFRP exhibited high effectiveness in waterproofing and repair of damaged RC structures. Applicability of epoxy injection in local repair of cracked RC specimens was confirmed, while failure of epoxy resulted in substantial growth in crack width and leakage rate of the panel.